2021
DOI: 10.1177/10497315211052639
|View full text |Cite
|
Sign up to set email alerts
|

Staff Wellbeing and Retention in Children’s Social Work: Systematic Review of Interventions

Abstract: Objective: To systematically review international evidence on the effectiveness and cost-effectiveness of interventions targeting the mental health, wellbeing, and retention of child and family social workers and their impact on child and family outcomes.Method:Systematic review and narrative synthesis of quantitative comparative studies. Published or unpublished research was sought via 12 bibliographic databases, websites, contact with experts, and citation tracking. Studies in any language were eligible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…Almost one-third of respondents (32%) in the present study reported a medium to high level of turnover intention, which is consistent with several findings on actual turnover rate among mental health and child welfare staff [ 13 , 45 , 69 73 ]. Since turnover intention is a strong cognitive precursor of actual turnover behavior [ 8 , 74 ], the present findings can be alarming and should be addressed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Almost one-third of respondents (32%) in the present study reported a medium to high level of turnover intention, which is consistent with several findings on actual turnover rate among mental health and child welfare staff [ 13 , 45 , 69 73 ]. Since turnover intention is a strong cognitive precursor of actual turnover behavior [ 8 , 74 ], the present findings can be alarming and should be addressed.…”
Section: Discussionsupporting
confidence: 92%
“…Although therapist directed interventions like this or mindfulness training can help, previous studies have shown that organizational interventions are more alterable and are more efficient in reducing burnout and increase personal efficacy [ 6 ]. Work-related measurements can include promoting and facilitating trauma training and utilization of EBPs; reducing case overloads, role conflict and ambiguity; increasing possibilities for job autonomy, social support, and supervision, adapting regular screening systems for early detection of individuals at risk, as well as reforming the organizational climate and the leadership style [ 25 , 36 , 38 , 73 , 86 ]. However, as mentioned, focusing on factors associated with burnout should receive high priority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social worker health and well-being has been a focus for research with the impact of working conditions and work-related stress and burnout of particular interest (Beer et al, 2020 ). Social work is a stressful occupation with many aspects of the job proving stressful or, at times, overwhelming for practitioners dealing with substantial caseloads, bureaucratic structures, reducing resources, constant policy changes, staff shortages, client trauma, public scrutiny, and a blame culture (Kinman et al, 2020 ; Turley et al, 2021 ). Perhaps it is unsurprising that social workers have been found to be at higher risk of stress and ultimately burnout because of their job role, particularly when compared to other occupations (Kinman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps it is unsurprising that social workers have been found to be at higher risk of stress and ultimately burnout because of their job role, particularly when compared to other occupations (Kinman et al, 2020 ). Indeed, Turley et al ( 2021 ) point to evidence suggesting UK social workers have an average working life span of < 8 years compared to their healthcare counterparts in nursing (16 years) and medicine (25 years). The current COVID pandemic has served to intensity pressures, adversely impacting the well-being of frontline/essential health and social care practitioners (Hosseinzadeh Asl, 2021 ).…”
Section: Introductionmentioning
confidence: 99%